Method of traffic optimization of urban passenger transport at transfer nodes - Vdovychenko, Volodymyr; Driuk, Oleksandr; Samchuk, Ganna (Eastern-European Journal of Enterprise Technologies, 2017)
The method of optimization of traffic of urban passenger transport (UPT) at transportation hubs (TH) is proposed, which implies modeling of operation of a stop point, taking into account individual characteristics of traffic parameters and time of servicing the vehicles. Software implementation of the simulation model is created in the PyCharm environment. The algorithm of the program includes a procedure for the formation of all possible combinations of shifting of time of departure of vehicles from the starting stop point within the traffic interval on the UPT routes, which pass through TH. For every combination, calculation of waiting time and of the number of vehicles in a queue is performed. Employing the minimal values of these indicators, we choose a combination that provides optimal coordination of traffic at TH for each number of service places at a stop point. Efficiency of the algorithm in the lookup and assessment of all possible combinations of values of input factors, implied by the presented method of optimization, may be guaranteed if the following limitations are satisfied: the number of routes is up to 5, traffic interval is up to 30 min. Based on results of the studies, it was established that it is possible to decrease unproductive downtime by up to 50 % even for a single service place if a change is made in the traffic schedule for the purpose of synchronization. In addition, when adding one service place, we observed a nonlinear decrease in the waiting time of vehicles in a queue